Social support and loneliness: Reflections on the elderly population in institutional and community context - Amaro da Luz, Maria Helena Reis (2015)
Aims: The support from social networks reflects different satisfaction levels among the elderly, which are associated with contextual variables, providing at the same time readings on the prediction of loneliness. Thus, the objectives of this study are: to distinguish the social networks of the elderly in the sample, discuss the levels of satisfaction towards social support networks and the perception related to feelings of loneliness, based on the influence of residential context. Additionally, the subjective perception of loneliness will be retained, to analyze the explanatory models that are hierarchically underlined. Method: The sample was composed of 221 elderly, of which 99 (44.8%) living in the community and 122 (55.2%) living in an institution. The protocol was composed of: Sociodemographic Questionnaire; Lubben Social Networks Scale; Social Support Satisfaction Scale (ESSS); and UCLA Loneliness Scale. Findings: The comparison of social support networks amongst participants revealed the existence of statistically significant differences in all considered dimensions: community residents have a wider family, friends, and confidants support network than institution residents. Subsequent tests show statistically significant differences in domains related to friends, family, and social support, showing community residents to be the most satisfied. The multiple regression reveals additions in the explained variance of loneliness, as the final model shows that satisfaction with family, the presence of confidants, and friend networks are important predictors of loneliness. Conclusions: Compared to participants living in institution, the elderly living in the community report higher levels of received social support, as well as perceived social support. By itself, the residential context does not affect the subjective perception of loneliness. However, when the institutionalization context is focused, the received social support and related satisfaction are found to be important contributions to minimize elderly loneliness.